Outbreak Investigation of Unusual Deaths in Cases of Acute Hepatitis Syndrome, in Makronia Municipal Area of Sagar Disitrict of Madhya Pradesh - Sunil Kant Guleri; Amarnath Gupta; Sunil Nandeshwar; Shraddha Mishra; Ramkumar Panika; Rupesh Sahu (Medsci Publications, 2019)
Introduction: Eleven (11) cases of sudden deaths were reported in patients suffering from jaundice in Sagar district of Madhya Pradesh during March-July 2018. All the cases were HBsAg posi- tive and died due to hepatic encephalopathy and or hepatorenal failure. Methods: outbreak investigation was done using semi-structured profarma. The clinical history, investigation reports, death certifi- cates and other available documents were analysed and findings recorded. House to house survey and health camps were also or- ganised to find other cases with similar illnesses. The blood sam- ples family members and suspected cases with jaundice were sent to ICMR NIRTH Jabalpur for viral isolations. Results: All the cases of deaths were localised within an area of about 10 Kms. About 72% cases recorded died within 3 days of ill- ness. Jaundice, abdominal pain and vomiting were the common symptoms. All cases were Hepatitis b surface antigen (HBSAg ) test +ve, SGPT raised in 90.90 % cases, SGOT raised in 81.82 cases. Conclusion: In ICMR NIRTH Jabalpur, reports leptospira positivity was found in 05 cases. There was no other underlying cause except Leptospira co-infection/super-infection which was responsible for such a high fatality in cases with acute Hepatitis.